Diagnostic accuracy of pelvic examination in pelvic inflammatory disease: A meta‐analysis - Hiroyoshi Iwata; Yoshifumi Sugiyama; Yoshinao Satoi; Naoko Sasamoto; Takuya Aoki; Masato Matsushima (Journal of General and Family Medicine, 2022)
Abstract Background Pelvic inflammatory disease (PID) is not a mere transient infection. PID can lead to chronic pain, ectopic pregnancy, and infertility. Although the Centers for Disease Control and Prevention have established minimum diagnostic criteria, including pelvic examination, the diagnostic value of pelvic tenderness has recently garnered controversy. Our meta‐analysis aimed to confirm whether pelvic tenderness, cervical motion tenderness, and adnexal tenderness can help diagnose PID. Methods We searched for studies reporting the diagnostic test accuracy of pelvic tenderness, cervical motion tenderness, and adnexal tenderness among female patients at risk for PID, using MEDLINE, EMBASE, CENTRAL, CINAHL, Google, and Google Scholar through May 25th, 2022. After quality assessment using QUADAS‐2, we performed data synthesis using a bivariate random effect model and Bayesian hierarchical summary receiver operating characteristic model. We then conducted sensitivity analysis excluding studies with non‐PID cases. Results The literature search produced 6769 articles. After quality assessment, 14 studies and their 2808 participants were eligible for synthesis on pelvic tenderness. Laparoscopy, either alone or in combination, was the most frequent reference standard. The main results for pelvic tenderness sensitivity and specificity were 0.81, 95% confidence interval (CI) [0.67–0.90] and 0.40, 95% CI [0.25–0.57], respectively. Sensitivity and specificity were 0.72, 95% CI [0.57–0.83] and 0.50, 95% CI [0.34–0.66], for cervical motion tenderness, and 0.87 [0.64–0.96] and 0.27, 95% CI [0.12–0.52] for adnexal tenderness, respectively. Conclusions Our meta‐analysis suggests that pelvic tenderness assessed by pelvic examination may be useful for PID examination with moderate‐to‐high sensitivity, whereas clinicians should be aware of the diagnostic significance of pelvic tenderness.